News Aggregators, Volatility and the Stock Market - Hans Byström (Lund University, School of Economics and Management, Department of Economics, 2009)
In this paper we employ the news aggregator GoogleTM News to demonstrate a strong link between the volatility in the stock market and the amount of news available to market participants. The paper also highlights some other areas, in finance and elsewhere, where news aggregators could be useful.
Keywords: C82; D80; G10; 330; news aggregator; volatility